Immunological mechanisms in steatotic liver diseases: An overview and clinical perspectives - Mengyao Yan; Shuli Man; Long Ma; Lanping Guo; Luqi Huang; Wenyuan Gao (Clinical and Molecular Hepatology)
Steatotic liver diseases (SLD) are the principal worldwide cause of cirrhosis and end-stage liver cancer, affecting nearly a quarter of the global population. SLD includes metabolic dysfunction-associated alcoholic liver disease (MetALD) and metabolic dysfunction-associated steatotic liver disease (MASLD), resulting in asymptomatic liver steatosis, fibrosis, cirrhosis and associated complications. The immune processes include gut dysbiosis, adiposeliver organ crosstalk, hepatocyte death and immune cell-mediated inflammatory processes. Notably, various immune cells such as B cells, plasma cells, dendritic cells, conventional CD4+ and CD8+ T cells, innate-like T cells, platelets, neutrophils and macrophages play vital roles in the development of MetALD and MASLD. Immunological modulations targeting hepatocyte death, inflammatory reactions and gut microbiome include N-acetylcysteine, selonsertib, F-652, prednisone, pentoxifylline, anakinra, JKB-121, HA35, obeticholic acid, probiotics, prebiotics, antibiotics and fecal microbiota transplantation. Understanding the immunological mechanisms underlying SLD is crucial for advancing clinical therapeutic strategies.